Ortaöğretim coğrafya derslerinde coğrafi bilgi sistemleri (CBS) tabanlı projelerin uygulanması: Bahçelievler ilçesi aydınlatma haritasının çıkarılması örneği - Armutcu, Murat (My University, 2013)
Bu çalışma ortaöğretim coğrafya derslerinde Coğrafi Bilgi Sistemleri (CBS) tabanlı projelerin uygulamasının önemini vurgulamak, öğrencilerin CBS tabanlı projelere karşı tutumlarını ortaya koymak amacıyla hazırlanmıştır. Çalışma, ortaöğretim öğrencilerinin görüşlerinin incelenmesine yönelik bir araştırmadır. Çalışmanın evrenini İstanbul İli Bahçelievler İlçesi ve bu ilçede bulunan Prof. Dr. Mümtaz Turhan Sosyal Bilimler Lisesi oluşturmaktadır. Çalışmada veri toplamak amacıyla, ilk aşamada öğrencilerle birlikte İstanbul İli Bahçelievler İlçesi Aydınlatma Haritasının Hazırlanması isimli örnek bir proje uygulaması yapılmıştır. İkinci aşamada ise öğrencilere yönelik iki anket geliştirilmiştir. Bu anketler projede görevli 15 öğrenciye uygulanmış ve sonuçlar tablolar halinde hazırlanmıştır. Sonuç olarak coğrafya derslerinde CBS tabanlı projelerin uygulanması öğrencilerin coğrafya derslerine karşı ilgi ve alakalarının artmasını, konuların daha anlaşılır bir hale gelmesini sağlamaktadır. Öğrenciler CBS’nin coğrafya bilimi ve toplumsal sorunların çözümü için ne denli önemli bir araç olduğunu uygulayarak görmüşlerdir. Proje ile öğrenciler mekânın anlaşılması, yorumlanması ve yönetilmesinde CBS’nin rolünü açıkça görmüşler ve bu teknolojilerden coğrafya derslerinde daha fazla yararlanılması gerektiğini düşünmüşlerdir. rafi Bilgi Sistemleri, Proje, Coğrafya dersleri, Ortaöğretim

GEOGRAPHIC INFORMATION ADEQUACY OF SOCIAL STUDIES IN THE ELEMENTARY SCHOOL AND THE EFFECT OF GEOGRAPHY LESSONS IN THE SECONDARY SCHOOL Advanced geography education is a necessity for individuals who are able to understand better their environment, perceive events that occur in nature and establish links between natural events that occur around them. Although geography is a part of social studies in elementary school system in our country, the lack of integrity of geography subjects, the lack of any geography related course in the 8th grade, the combination of history, geography, sociology, anthropology, humanities and citizenship under a single course which is called social studies and above all, social studies teachers inadequate geography knowledge cause lack of knowledge in geography for 9th grade students. It also creates learning disability for 9th grade students which decreases learning efficiency in secondary school. Corrospondingly, geography teachers in the secondary school have difficulties to teach the course. This research is aimed to investigate geography information adequacy of social studies curriculum in the elementary school whether there is sufficient information for secondary school students. For this purpose, two primary and two secondary schools in the province of Istanbul were selected including 120 primary and 120 secondary school students who completed the questionnaire. Surveys were taken by students who have completed 7th level in elementary school and students who have started 9th level in secondary school. In addition, the interviews were conducted with eight different social studies and geography teachers to obtain the feedback in the same institutions. The result of the study was evaluated with the help of SPSS and the data of the result was presented in tables and graphs. Depending on the findings of the two solutions is proposed. The first solution is based on balanced geography courses among subjects instead of reducing courses for 7th grade, geography subject integrity under social studies cirriculum in elementary school, 8th grade geography classes and using the correct methods of teaching vii geography class by social studies teachers emphasizing importance of geography class. Second, geography from the beginning of primary school is instructed as a separate subject rather than one course under social studies including history,sociology, anthropology, humanities and citizenship courses. Key Words: Primary Social Studies course, secondary school geography lesson, student, teacher
Keywords: Coğrafya_Öğrenim ve Öğretim; Eğitim; Öğrenim ve Öğretim